The effect of using the selective model in teaching chemistry on the achievement of fifth grade middle school students (Journal of the College of Basic Education, 2025)
The current study seeks to identify the effect of using the eclectic model in teaching chemistry on the achievement of fifth-grade middle school students. The researcher adopted the quasi-experimental approach as an approach to the current study by designing a control group with a pre- and post-test. In order to achieve the objectives of the current study, the researcher built an achievement test to measure the level of achievement of fifth-grade middle school students in chemistry, and to verify the validity and reliability of the test, as well as Conducting a set of equivalences between both groups and after applying the experiment, the study reached the following results:The selective model has a clear effect in raising the achievement level of chemistry for the experimental groupThere are statistically significant differences between the experimental and control groups, and these differences are in favor of the experimental group